IELTS express : - Hallows, Richard (Thomson, 2006)
IELTS Express Upper Intermediate is the second level of a two-level IELTS exam preparation series. Level two is designed for students at IELTS band 5.5 and above, providing a mid-level entry-point for students wishing to prepare for IELTS. Each IELTS express coursebook is ideal for short preparation courses of 30-40 hours, and can easily be extended for longer courses by selecting from supplementary materials including the Workbook and Video/DVD.